Comprehensive Understanding of Fa-sʿaw ilā Dhikrillāh in Qur’an 62:9 - Rashid, Md. Mamunur (Journal of Quranic Sciences and Research, 2026)
Qur’an 62:9 directs Muslims: “O you who believe, when the call is proclaimed for prayer on Friday, hasten to the remembrance of Allah (fa-sʿaw ilā dhikrillāh) and leave off trade.” This verse establishes the principal Qur’anic basis for the obligation of attending the Friday congregational prayer. However, the exact meaning of the phrase fa-sʿaw ilā dhikrillāh has been interpreted differently by classical and contemporary scholars. Some scholars interpret fa-sʿaw in this verse as meaning “hasten,” while others prefer the meaning “proceed.” Likewise, dhikr has been interpreted differently: some scholars view it as referring collectively to both the khutbah and the ṣalāh, whereas others maintain that it specifically denotes the khutbah. This difference of explanation has important implications for understanding the scope of the Qur’anic command and the significance of attentive listening to the Friday sermon. This study presents a comprehensive understanding of the phrase fa-sʿaw ilā dhikrillāh in Qur’an 62:9 by analyzing its linguistic, contextual, and exegetical dimensions. It explores the lexical meanings of the words saʿā and dhikr in Qur’anic usage and examines interpretations in major classical tafsir works and relevant Prophetic traditions. Particular attention is given to hadiths describing the presence of angels during the khutbah and the Prophet’s mention of the sermon as dhikr, which provides important guidance for understanding the Qur’anic expression. The study demonstrates that interpreting the command of this verse as “hasten to attend the khutbah” offers a more coherent understanding. This conclusion emerges when the linguistic explanation of fa-sʿaw, the Qur’anic usage of fa-sʿaw, the hadiths of the Prophet (PBUH), and the historical circumstances of the revelation are considered together. By clarifying the meaning of this Qur’anic directive, the study highlights the religious and communal importance of the Friday sermon in Islamic practice.